Simple and universal synthesis of sulfonated porous organic polymers with high proton conductivity. (17th June 2020) - Li, Zhongping; Yao, Yuze; Wang, Dongjin; Hasan, Md. Mahmudul; Suwansoontorn, Athchaya; Li, He; Du, Gang; Liu, Zhaohan; Nagao, Yuki
Abstract : By using a simple and universal process, we successfully synthesized various sulfonated porous organic polymers with high proton conductivity, and therefore this strategy could evolve structural designs for high proton-conductive materials. Abstract : Along with the rapid development of economic integration and regional economization worldwide, the growth of green and sustainable resources has posed a major concern. Proton-exchange membrane fuel cells (PEMFCs) are examples of green, resource-conserving, and environmentally protective energy resources. Porous organic polymers (POPs), a new class of porous materials with high porosity, permanent pores, excellent stability, and easily modified functional units, can offer a good platform as proton-conducting electrolytes for fuel cells. However, a simple and general design to construct POPs with high proton conductivity presents a challenging project. For this study, we used simple benzene and aromatic benzene as building units through a facile and cost-effective process to create a series of POPs. We further prepared sulfonated POPs (S-POPs) with high-density sulfonic acid groups via post-sulphonation. The S-POPs displayed excellent proton conductivity up to 10 −2 S cm −1 at 25 °C and 95% relative humidity (RH), and high conductivity up to 10 −1 S cm −1 at 80 °C and 95% RH, which ranked top among the most proton-conducting POPs. These results suggest that construction of S-POPs offers a simple and universal way to evolve structural designs for high proton-conductive materials.